Single cell autofluorescence imaging reveals immediate metabolic shifts of neutrophils with activation across biological systems - Datta, Rupsa; Miskolci, Veronika; Gallego-López, Gina M.; Britt, Emily; Gillette, Amani; Kralovec, Aleksandr; Giese, Morgan A.; Qian, Tongcheng; Votava, James; Zhao, Wenxuan; Fan, Jing; Huttenlocher, Anna; et al. (Frontiers in Immunology, 2025)
IntroductionNeutrophils are critical innate immune cells that heterogeneously respond to infection and inflammation by performing functions such as oxidative burst and NETosis, which require significant metabolic adaptation. Deeper insights into the single cell diversity of such metabolic changes will help identify regulation of neutrophil functions in health and diseases. Due to their short lifespan and associated technical challenges, the early metabolic processes of neutrophil activation are not completely understood. New tools are needed to measure rapid changes in neutrophil metabolism on a single cell level.MethodsTo address this, we use optical metabolic imaging (OMI), which entails optical redox ratio and fluorescence lifetime imaging microscopy of intrinsic metabolic coenzymes NAD(P)H and FAD to assess the metabolic state of single neutrophils. Primary human neutrophils were imaged in vitro under a variety of activation conditions and metabolic pathway inhibitors, while metabolic and functional changes were confirmed with mass spectrometry, oxidative burst, and NETosis measurements.ResultsOur findings show rapid metabolic remodeling to a reduced redox state during activation. Additionally, heterogeneous metabolic response to pathogens (Pseudomonas aeruginosa and Toxoplasma gondii) was observed across neutrophils and human donors. Finally, consistent OMI changes with activation were confirmed between in vitro human and in vivo zebrafish larvae neutrophils. This study demonstrates the potential of OMI as a versatile tool for studying neutrophil metabolism and underscores its use across different biological systems, offering insights into neutrophil metabolic activity and function at a single cell level.ConclusionThis work addresses the critical need for advanced single-cell tools to monitor rapid and diverse metabolic changes in neutrophils, an underexplored area with significant implications for understanding immune responses and developing therapies for inflammatory diseases. Neutrophils, the body's first responders to infection and inflammation, undergo rapid metabolic changes upon activation. Using label-free optical metabolic imaging of intrinsic metabolic coenzymes NAD(P)H and FAD, we reveal distinct metabolic signatures in activated primary human neutrophils as well as neutrophils in live zebrafish larvae. Our findings highlight how pathogens and pharmacological stimuli heterogeneously rewire neutrophil metabolism within minutes, influencing immune responses. This noninvasive method offers insights into single-cell neutrophil metabolism immediately following activation, with implications for infection, inflammation, and immune disorders.